Rethinking teacher supervision and evaluation : how to work smart, build collaboration, and close the achievement gap - Marshall, Kim (San Francisco, California : Jossey-Bass Inc., Publishers, 2009)
Teacher supervision and evaluation practices can serve as powerful levers for improving teaching, but few school leaders know how to go about implementing practices that are fair and constructive. This book introduces a principles-based framework for supervising teachers and evaluating their performance for achieving optimal results. This approach does not make test results part of the teacher's evaluation. Instead, it encourages teachers to focus on student learning and test results in ways that are candid, honest, and productive. This is an invaluable aid for principals, instructional leaders, and teacher coaches.
1. The challenge : closing the achievement gap -- 2. Supervision and evaluation : why we need a new approach -- 3. Mini-observations 1 : a system is born -- 4. Mini-observations 2 : suggested best practices -- 5. Curriculum design : the foundation of good teaching -- 6. Interim assessments : using results to continuously improve instruction -- 7. Rubrics : potent, time-efficient evaluation tools -- 8. Time management : doing first things first -- 9. Putting it all together.
Includes bibliographical references and index.
Keywords: PERFORMANCE STANDARS